Sistem Status Kelaikudaraan Pesawat Udara Berbasis Website Menggunakan Framework CodeIgniter dan PostgreSQL dengan Metode Prototype - Abdul Aziz; Ildefonsa Anna Fransiska Nahak; Irma Rismayanti; Aries Asrianto Ramadian; Danartomo Kusumoaji; Nurul Lailatul Muzayadah; Rudi Choirul Anwar (Teknik Informatika Universitas Pamulang, 2020)
In aircraft operation, maintenance must always be carried out so that the aircraft meets airworthiness standards in order to meet flight safety, in which maintenance is carried out on aircraft components on a regular basis. The problem that exists today is that there is frequent damage to the aircraft without any known cause, even when the aircraft is flown which results in the plane crashing and experiencing severe damage until it can no longer be used. This condition is due to the absence of a system that can monitor the aircraft maintenance process, so that the components of the aircraft used to be flown cannot be known whether it is airworthy or not. The solution to overcome this problem is by building a website-based system. The system was built using the CodeIgniter framework and PostgreSQL as its database. Meanwhile, for system development using the Prototype method. Through this system the aircraft maintenance process can be carried out according to the existing schedule.